2016
DOI: 10.1093/fampra/cmw091
|View full text |Cite
|
Sign up to set email alerts
|

The psychometric properties of the Hopkins Symptom Checklist-10: a Rasch analysis based on adolescent data from Norway

Abstract: The HSCL-10 has the potential to measure the psychological distress among adolescents but there is a room for improvement. Further judgement needs to be made as to whether the misfitting item 'Sleeping difficulties' should be removed or retained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
47
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 21 publications
9
47
1
2
Order By: Relevance
“…The respondents had to answer at least seven out of 10 items in order to get a valid score on the scale (35). HSCL-10 is a wellused and validated scale among adolescents (34,35). Cronbach's alpha for the scale in the present study was .92 (T1) and .93 (T2).…”
Section: Assessmentsmentioning
confidence: 63%
See 1 more Smart Citation
“…The respondents had to answer at least seven out of 10 items in order to get a valid score on the scale (35). HSCL-10 is a wellused and validated scale among adolescents (34,35). Cronbach's alpha for the scale in the present study was .92 (T1) and .93 (T2).…”
Section: Assessmentsmentioning
confidence: 63%
“…Symptoms of anxiety and depression: The 10-item version of Hopkins Symptom Checklist was used to assess symptoms of depression and anxiety (HSCL-10) (34,35). Six of the 10 items are related to depression, and four are related to anxiety (34), rated on a fourpoint scale ranging from (1) Not at all to (4) Extremely; higher mean scores indicate a higher severity of anxiety and depression symptoms. The respondents had to answer at least seven out of 10 items in order to get a valid score on the scale (35).…”
Section: Assessmentsmentioning
confidence: 99%
“…HSCL-10 is a short version of the Hopkins Symptom that is used to measure symptoms of depression and anxiety (Derogatis et al, 1974;Strand et al, 2003). Studies targeted toward youth have widely utilised this instrument (Haavet, Sirpal, Haugen, & Christensen, 2010;Kleppang & Hagquist, 2016;Strand et al, 2003;Søgaard, Bjelland, Tell, & Røysamb, 2003).…”
Section: The Questionnairementioning
confidence: 99%
“…A cutoff score of 1,75 is used to identify whether the clinical symptoms presented are classified as significant or not (Lhewa et al, 2007). Previous studies found that HSCL was a valid and reliable measure for adolescents when the value of Cronbach's α ranged from 0.85-0.91 (see Kleppang & Hagquist, 2016).…”
Section: Methodsmentioning
confidence: 99%